Effect of smear layer deproteinization with HOCl solution on the dentin bonding of conventional and resin-modified glass-ionomer cements - Paing, Soe Yu; Tichy, Antonin; Hosaka, Keiichi; Nagano, Daiki; Nakajima, Masatoshi; Tagami, Junji (European journal of oral sciences, 2020)
The effect of smear layer-deproteinizing pretreatment using hypochlorous acid (HOCl) on the micro-shear bond strengths (μSBS) of conventional and resin-modified glass-ionomer cements (GIC) to dentin was investigated and compared with demineralizing pretreatment with polyacrylic acid (PAA). Three GICs: Fuji IX GP Extra (restorative conventional GIC), GC Fuji II LC EM (restorative resin-modified GIC), and GC Fuji Luting EX (luting resin-modified GIC), were used. One hundred fifty human molars were divided into groups (n = 10) according to the cements and dentin pretreatments; no pretreatment (control), 10 s PAA pretreatment, and HOCl pretreatment for 5, 15, or 30 s. After 24 h, μSBS was tested and the data were statistically analyzed using a two-way ANOVA, followed by Tukey's post-hoc test. HOCl pretreatment significantly increased μSBS of conventional GIC compared to the control group. For resin-modified restorative GIC, 5 s HOCl deproteinization significantly increased μSBS, while longer application times did not. There was no significant difference between HOCl-pretreated and control groups of resin-modified luting GIC. PAA pretreatment increased the μSBS of all cements significantly. In conclusion, smear layer deproteinization with HOCl can enhance the dentin bonding of conventional GIC. However, the residual radicals may adversely affect the polymerization of resin-modified GICs.
Keywords: dentin; Hypochlorous Acid; vazba zubní; Dental Bonding; kyselina chlorná; Dentin; Resin Cements; složené pryskyřice; smear layer; Humans; Smear Layer; Composite Resins; testování materiálů; Glass Ionomer Cements; Materials Testing; skloionomerní cementy; lidé; pryskyřičné cementy